Equitable identification of gifted students with the relationship of religiosity and ethical sensitivity level of teachers. (January 2023) - Lee, Hyeseong; Wilkins, Martha A.; O'Brien, Ann
As teachers are the gatekeepers in identification procedure, it is crucial to understand how teachers' openness and beliefs may affect the equitable identification. To be specific, we focused on how teachers' level of religious beliefs and ethical sensitivity impact notions of fairness in the identification of gifted students, particularly those from traditionally underrepresented groups. Study participants were 46 teachers who attended a Midwestern Catholic University in the U.S. Based on the results measuring teachers' religiosity, ethical sensitivity, and equitable identification index from vignettes, we found that there were no statistically significant score differences of religiosity and ethics level of teachers when they were divided into two groups, one showing equitable identification versus the other comparatively not. However, the majority of teachers (70%) fairly identified students regardless of their religiosity, ethical sensitivity, school experiences, confidence level serving gifted students, and current academic status when the vignettes had different students' race and family income status information.